Complete mitochondrial genome sequence of an aflatoxin B and G producing fungus, Aspergillus parasiticus. Issue 1 (2nd January 2019) - Park, Jongsun; Kwon, Woochan; Zhu, Bohan; Mageswari, Anbazhagan; Heo, In-Beom; Kim, Jong-Hwa; Han, Kap-Hoon; Hong, Seung-Beom
Abstract: Aspergillus parasiticus is a notorious filamentous fungus, which can produce aflatoxin B and G. Here, we reported the complete mitochondrial genome sequence of Aspergillus parasiticus isolated from air in South Korea. Its mitochondrial genome was successfully assembled from raw reads sequenced using MiSeq by Velvet and GapCloser. Total length of the mitochondrial genome is 29, 141 bp and encoded 45 genes (17 protein-coding genes, 2 rRNAs, and 26 tRNAs). Nucleotide sequence of coding region takes over 25.4% and overall GC content is 26.2%. Phylogenetic tree presents that A. parasiticus is clustered with Aspergillus oryzae, which is same section Flavi in Aspergillus genus. It will be a useful molecular resource to understand section Flavi in Aspergillus genus.